2004
DOI: 10.1517/13543776.14.7.1009
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in 5-HT7receptors: potential treatment of central and peripheral nervous system diseases

Abstract: In light of the barrage of recent reviews on 5-HT 7 receptor agonists and antagonists, this article will highlight and review the research advances published in the patent literature between January 1997 and December 2003. The article is supplemented with selected references on the design, synthesis and development of novel 5-HT 7 agents to treat central and peripheral nervous system diseases. Emphasis is placed on recent advances in the possible involvement of 5-HT 7 serotonergic agents in the treatment of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The recent development of 5-HT 7 receptor-selective antagonists and the generation of a 5-HT 7 knock-out mouse (Hedlund et al, 2003) have accelerated the investigation of the role of the 5-HT 7 receptor in brain function. Evidence is increasing which suggests a role for the 5-HT 7 receptor in the control of circadian rhythms and sleep (Lovenberg et al, 1993;Thomas et al, 2003;Slassi et al, 2004;Sprouse et al, 2004;Thomas and Hagan, 2004). In correlation herewith is the postulated role for the 5-HT 7 receptor in depression.…”
Section: Introductionmentioning
confidence: 79%
“…The recent development of 5-HT 7 receptor-selective antagonists and the generation of a 5-HT 7 knock-out mouse (Hedlund et al, 2003) have accelerated the investigation of the role of the 5-HT 7 receptor in brain function. Evidence is increasing which suggests a role for the 5-HT 7 receptor in the control of circadian rhythms and sleep (Lovenberg et al, 1993;Thomas et al, 2003;Slassi et al, 2004;Sprouse et al, 2004;Thomas and Hagan, 2004). In correlation herewith is the postulated role for the 5-HT 7 receptor in depression.…”
Section: Introductionmentioning
confidence: 79%
“…Subsequently a number of pharmaceutical companies and academic research groups reported the identification of selective 5-HT 7 R ligands and excellent reviews in the field were provided during 2004 [62,64]. Briefly, some of the most interesting ligands worth of mention are: tetrahydroquinolines from Roche, aporphine derivatives from Uppsala University, aminoalkylpirrolidines and amidinoureas from Pfizer, 6-bromo-1-substituted-ethylindoles from NPS Pharmaceuticals, carbocyclic sulfonamide derivatives and dimethyl-(2-arylsulfanylethyl)amines from Merck & Co. Inc. [93][94][95][96][97][98][99][100][101].…”
Section: -Ht 7 Receptor Ligandsmentioning
confidence: 99%
“…The pharmacological aspects of 5-HT 7 Rs have been reviewed in 2004 [62,63,65,66]. Initial progresses in the elucidation of potential therapeutic function of 5-HT 7 Rs have been made using unselective ligands in the presence of masking agents.…”
Section: Potential Therapeutic Implications For 5-ht 7 Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation